Waterborne Norovirus outbreak at a seaside resort likely originating from municipal water distribution system failure. Issue 7 (10th April 2018) - Giammanco, G. M.; Bonura, F.; Urone, N.; Purpari, G.; Cuccia, M.; Pepe, A.; Li Muli, S.; Cappa, V.; Saglimbene, C.; Mandolfo, G.; Marino, A.; Guercio, A.; et al.
Abstract: In May 2016 a Norovirus (NoV) gastroenteritis outbreak involved a high school class visiting a seaside resort near Taormina (Mascali, Sicily). Twenty-four students and a teacher were affected and 17 of them showed symptoms on the second day of the journey, while the others got ill within the following 2 days. Symptoms included vomiting, diarrhoea and fever, and 12 students required hospitalisation. Stool samples tested positive for NoV genome by Real-Time polymerase chain reaction assay in all 25 symptomatic subjects. The GII.P2/GII.2 NoV genotype was linked to the outbreak by ORF1/ORF2 sequence analysis. The epidemiological features of the outbreak were consistent with food/waterborne followed by person-to-person and/or vomit transmission. Food consumed at a shared lunch on the first day of the trip was associated to illness and drinking un-bottled tap water was also considered as a risk factor. The analysis of water samples revealed the presence of bacterial indicators of faecal contamination in the water used in the resort as well as in other areas of the municipal water network, linking the NoV gastroenteritis outbreak to tap water pollution from sewage leakage. From a single water sample, an amplicon whose sequence corresponded to the capsid genotype recovered from patients could be obtained.